Peripheral dose around a mobile linac for intraoperative radiotherapy: radiation protection aspects. (29th October 2018) - García-Cases, F; Perez-Calatayud, J; Ballester, F; Vijande, J; Granero, D
Abstract: The aim of this work is to analyse the scattered radiation produced by the mobile accelerator Mobetron 1000. To do so, detailed Monte Carlo simulations using two different codes, Penelope2008 and Geant4, were performed. Measurements were also done. To quantify the attenuation due to the internal structures, present in the accelerator head, on the scattered radiation produced, some of the main structural shielding in the Mobetron 1000 has been incorporated into the geometry simulation. Results are compared with measurements. Some discrepancies between the calculated and measured dose values were found. These differences can be traced back to the importance of the radiation component due to low energy scattered electrons. This encouraged us to perform additional calculations to separate the role played by this component. Ambient dose equivalent, H*(10), outside of the operating room (OR) has been evaluated using Geant4. H*(10) has been measured inside and outside the OR, being its values compatible with those reported in the literature once the low energy electron component is removed. With respect to the role played by neutrons, estimations of neutron H*(10) using Geant4 together with H*(10) measurements has been performed for the case of the 12 MeV electron beam. The values obtained agree with the experimental values existing in the literature, being much smaller than those registered in conventional accelerators. This study is a useful tool for the clinical user to investigate the radiation protection issues arising with the use of these accelerators in ORs without structural shielding. These results will also enable to better fix the maximum number of treatments that could be performed while insuring adequate radiological protection of workers and public in the hospital.